Efeitos imediatos da eletroestimulação nervosa transcutânea e crioterapia na espasticidade e na atividade eletromiográfica de sujeitos hemiparéticos - Martins, Fábio de Lima (2009)
Cerebrovascular accident (CVA) is a term used to characterize an ischemic or hemorrhagic vascular injury, which has got as main clinic manifestations, the motor and reflex function disturbance. In the first stage there is flaccidity and loss of voluntary movements that afterwards is substituted by mass patterns and spasticity. The spasticity brings with itself functional deficits and can generate negative impacts in various motor patterns. The aim of this research was to investigate the hyperreflexia and identify the immediate effects of transcutaneous nervous stimulation (TENS) and cryotherapy in the spasticity and electromyographic activity of hemiparetic subjects. The study is characterized as an almost experimental type, in which were selected, to compose the sample, 16 patients of both sex with CVA sequel. These individuals were evaluated by collecting the amplitude peak to peak and H reflex latency, Motor response (M response) in solear muscle and the electromyography (EMG) of the injured and healthy legs anterior tibial muscles. In the injured limb the evaluations occurred in different days for cryotherapy, TENS and control, in two moments, before and after the interventions. The healthy limb was evaluated one single time to serve as baseline, for comparison with the injured limb. It was used an statistic analysis, the t paired student test to identify the H reflex differences, latency and EMG of the injured and healthy limbs and to compare the results before and after the recourses application. The ANOVA for related samples was used to identify the differences among the recourses used. It was attributed for the statistic tests a significance level of 5%. The amplitude peak to peak of normalized maximum H reflex through the maximum motor response (Hmax/Mmax), showed itself significantly increased in the injured limb (p=0.0245). The H reflex latency was presented reduced in the injured limb (p=0, 0375). The electromyographic activity was showed decreased in the injured limb (p< 0.0001). After the TENS there was a Hmáx/Mmáx ratio decrease (0.60±0.16 versus 0.49.±0.18; P = 0.0006). Nonetheless, Just after the cryotherapy application there was an increase of Hmáx/Mmáx ratio (0.58 ± 0,15 to 0.77 ± 0.13, P=0,0007) and increase of signal latency (30.41 ± 1.87 versus 33.24 ± 2.19; P=0.0001). The electromyographic activity wasn t altered significantly by any resource. It was met statistic significant differences when the Hmáx/Mmáx P<0.0001) ratio and H reflex latency (P<0.0001) were compared between the post TENS, cryotherapy and control. One can conclude that the TENS can be used to spasticity immediate reduction, and that the cryotherapy can increase the hyperreflexia state in spastic patients. Nonetheless, the spasticity decrease or increase didn t provoke lectromyographic activity change in the muscle that is opponent to the spastic one